Sitagliptin improves glycaemic excursion after a meal or after an oral glucose load in Japanese subjects with impaired glucose tolerance - Kaku, K. (Diabetes Obes Metab, 2015)
AIMS: To evaluate the efficacy and tolerability of sitagliptin in subjects with impaired glucose tolerance (IGT). METHODS: In a double‐blind, parallel‐group study, 242 Japanese subjects with IGT, determined by a 75‐g oral glucose tolerance test (OGTT) at week −1, were randomized (1 : 1 : 1) to placebo (n = 83), sitagliptin 25 mg (n = 82) or 50 mg (n = 77) once daily for 8 weeks. Glycaemic variables were assessed using another OGTT at week 7 and meal tolerance tests (MTTs) at weeks 0 and 8. Primary and secondary endpoints were percent change from baseline in glucose total area under the curve 0–2 h (AUC(0) (–2 h)) during the MTT and OGTT, respectively. RESULTS: Least squares mean percent change from baseline in glucose AUC(0) (–2 h) during the MTT were −2.4, −9.5 and −11.5%, and during the OGTT were −3.7, −21.4 and −20.1% with placebo, sitagliptin 25 mg once daily, and 50 mg once daily, respectively (p < 0.001 for either sitagliptin dose vs placebo in both tests). Sitagliptin treatment enhanced early insulin response during the OGTT and decreased total insulin response, assessed as the total AUC(0) (–2 h) during the MTT. Sitagliptin treatment also suppressed glucagon response during the MTT. The incidence of adverse events, including hypoglycaemia, was low and generally similar in all treatment groups. CONCLUSIONS: Treatment with sitagliptin significantly reduced glucose excursions during both an MTT and an OGTT; this effect was associated with an increase in early insulin secretion after oral glucose loading as well as a blunted glucagon response during an MTT. Sitagliptin was generally well tolerated in subjects with IGT.